How to take a Fortress? The Wrong and the Right Way: Preveza 1538 and 1605 - Pujeau, Emmanuelle (Πρεβεζάνικα Χρονικά, 2015)
In contrast with the failure of 1538 –the end of Christian supremacy on the sea– the Knights of St. Stephen easily took the fortress of Preveza in 1605 and illustrated how to do it successfully! The comparison of two apparently similar events provides new keys to understand them, althought the circumstances as well as the objectives of the two campaigns were drastically different. We will principally focus on the episode of the attack on the fortress, observing the similarities and differences between both events. The completely opposite outcomes of the two campaigns, illustrates the right and the wrong way to take a fortress in modern times.